Relative sensitivity to climate change of species in northwestern North America. (July 2015) - Case, Michael J.; Lawler, Joshua J.; Tomasevic, Jorge A.
Highlights: We assessed the relative sensitivity to climate change of 195 species. Amphibians and reptiles were the most sensitive to climate change of the taxa analyzed. A key driver of species' sensitivity is a dependence on climatically-sensitive habitats. Listed species tend to be more sensitive than those that do not. Species' sensitivity can be used to prioritize conservation and research needs. Abstract: Climate change affects plants and animals in myriad ways and to different degrees. Therefore, managing species in the face of climate change will require an understanding of which species will be most sensitive to future climatic changes and what factors will make them more sensitive. The inherent sensitivity of species to climate change is influenced by many factors, including physiology, life-history traits, interspecific relationships, habitat associations, and relationships with disturbance regimes. Using a combination of scientific literature and expert knowledge, we assessed the relative sensitivity to climate change of 195 plant and animal species in the northwestern North America. We found that although there were highly sensitive species in each of the taxonomic groups analyzed, amphibians and reptiles were, as a group, estimated to be the most sensitive to climate change. Not surprisingly, we found that the confidence that experts had in their assessments varied by species. Our results also indicate that many species will be sensitive to climate change largely because they depend on habitats that will likely be significantly altered as climates change. Although to date, many climate impact assessments for species have focused on projecting range shifts, quantifying physiological limits, and assessing phenological shifts, in light of our results, a renewed emphasis on the collection of basic natural history data could go a long way toward improving our ability to anticipate future climate impacts. Our results highlight the potential for basic information about climate-change sensitivity to facilitate the prioritization of management actions and research needs in the face of limited budgets.